1984
DOI: 10.1002/star.19840360106
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Steeping on the Chemical Structure of Corn Hull Hemicellulose

Abstract: The corn hull hemicellulose was isolated from unsteeped and for 30 and 60 h steeped grains. The hemicellulose was fractionated by Sephadex G‐100 column chromatography in order to compare the fraction constituents of each hemicellulose. Also the relative percentage and molar ratio of the sugars in each fraction were determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1987
1987
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…The process which has been described and has been studied by several authors [1,2], consists in the cooking of maize with a thermo alkaline treatment of lime (0.6-1.2%) of the weight of maize for a period of 50-70 min, which depend on the altitude over sea level as well as on the structure of the kernel, to be followed by a 12-14 h soaking time, the removal of the cooking liquor, 2 to 3 water washings of the kernel and grinding to a dough. Of the 3 main processing factors, alkali concentration, cooking/steeping time, and type of maize, the effects of lime have received some attention [4][5][6][7][8]. There is no information as how lime came to be used, although in the literature some times it is mentioned that the nixtamalization process was also carried out by using wood ashes instead of lime [25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The process which has been described and has been studied by several authors [1,2], consists in the cooking of maize with a thermo alkaline treatment of lime (0.6-1.2%) of the weight of maize for a period of 50-70 min, which depend on the altitude over sea level as well as on the structure of the kernel, to be followed by a 12-14 h soaking time, the removal of the cooking liquor, 2 to 3 water washings of the kernel and grinding to a dough. Of the 3 main processing factors, alkali concentration, cooking/steeping time, and type of maize, the effects of lime have received some attention [4][5][6][7][8]. There is no information as how lime came to be used, although in the literature some times it is mentioned that the nixtamalization process was also carried out by using wood ashes instead of lime [25].…”
Section: Introductionmentioning
confidence: 99%
“…It is instrumental in the break down of the seed coat in maize [7,8], but due to the alkaline pH, lime causes significant losses of carotenoids and B-Vitamins [9,10]. Some studies have shown lime to be useful in the increased bioutilization of niacin [11], and during the process there is a significant increase in Ca content [9,10,12,13], which is highly bioavailable [14][15][16]; it also reduces the levels of Fumonisin [17] and dietary fiber.…”
Section: Introductionmentioning
confidence: 99%
“…But to the best of our knowledge, there are only a few results on materials synthesized from polysaccharide wastes,5 particularly from maize bran. This latter substrate is constituted mainly of heteroxylans (45%) and cellulose (13%) 6. It is possible to extract heteroxylans by alkali treatments, and the residue is especially rich in cellulose, more than 50%.…”
Section: Introductionmentioning
confidence: 99%